Recent technologies to improve disease resistance against Botrytis cinerea - Ullah, Ikram; Mubeen, Mustansar; Iftikhar, Yasir; Shakeel, Qaiser; Abbas, Aqleem; Zeshan, Muhammad Ahmad; Khan, Shumaila; Godana, Esa Abiso; Wu, Hongzhi (Journal of Pure and Applied Agriculture, 2023)
Gray mold (Botrytis cinerea), is a significant postharvest disease of horticultural crops and can cause massive economic losses. It affects various plant organs including fruits, flowers, leaves, storage organs and shoots. Chemical fungicides are used as the first measure by most plant growers. However, due to their impact on the environment, the resistance of the pathogen to various chemicals, and consumer interest in organic consumption, alternative control strategies are increasingly being used. Recent studies are discussed on the improvement of fruit physiological aspects such as plant hormones and their signal transduction pathways playing a significant role in the defense against the necrotrophic fungus. Various phytohormones and plant elicitors can stimulate the defense response and control the outbreak of infection. Thus, these signaling molecules may be responsible for plant resistance and serve as substitutes for fungicides. The use of nanotechnology to enhance plant resistance to pathogens and the omics approach to induce disease resistance are pioneering studies to combat the disease. Crop genomics, metabolomics and transcriptomic studies are making important contributions to the identification of pathogen-plant interactions and the study of control mechanisms. The review suggests that the use of an integrated pest management approach could help overcome the high post-harvest food losses that the world has been facing recently. © 2022 Department of Agricultural Sciences, AIOU